Keterjangkauan Pelayanan Fasilitas Kesehatan Puskesmas Terhadap Persebaran Permukiman di Kabupaten Sumedang - Fazry Dhevio Harsyanutoro; Kanahaya Guntoro Putri; Mataburu, Ilham Badaruddin Mataburu (Prosiding Seminar Nasional Pendidikan, Ilmu-Ilmu Sosial, dan Hukum (SENPISHUM), 2026)
This study aims to analyze the spatial accessibility of community health center services to settlements in Sumedang Regency using a quantitative approach based on Geographic Information Systems (GIS). Buffering and intersect techniques are used to measure service coverage according to the ideal radius of the community health center based on SNI 03-1733-2004 of 3,000 meters. The results of the analysis show that some residential areas have been served by community health centers and there are still some areas that have not been reached. Settlements that have not been served are generally in areas with hilly topography, limited road networks, and uneven distribution of community health centers, such as in Ujungjaya, Tanjungmedar, and Conggeang Districts with an area of ​​2,860.287651 Ha. In contrast, densely populated areas such as North Sumedang and Jatinangor have better service accessibility or are still covered by an area of ​​7,821.981866 Ha. These findings emphasize the importance of spatial data-based planning to support equitable distribution of inclusive and sustainable health services. It is hoped that the results of this study can be the basis for policy making for the addition of health facilities and improvement of road infrastructure in Sumedang Regency.